Chiral separation of enantiomers of abscisic acid and jasmonic acid, by cyclodextrin-modified capillary electrophoresis - Tian, Liming. (2009)
Abscisic acid (ABA) and jasmonic acid (JA) are two types of plant hormones that control and regulate plant growth. Both of them have two enantiomers in synthetic compounds but only one of the structures exists in real plant body with low concentration. Chiral separation of ABA and JA has been so important in their biological studies and application that many chromatographic methods have been applied to achieve this in the past. Cyclodextrin-modified capillary electrophoresis (CE) has been one of the newest and most popular methods in chiral separation recently, because of its high efficiency and low cost. Only native cyclodextrins (CDs) have been used in the enantioseparation of ABA before, but charged CDs were also proved to be effective for many acids. Separation of JA enantiomers has not been achieved using CE yet. In this final year project, a synthetic positively charged CD named mon-6-N-pentylammonium-6-deoxy-β-CD chloride ([PA-CD][Cl]) was used as the selector to separate ABA successfully, and in comparison, another cationic CD and two native CDs were included. Effects of some important parameters of CE techniques were analyzed and discussed to optimize the separation resolution. Chiral separation of JA was not achieved yet after many different trials but potential methods were suggested for future work.